Lime Requirement Determination of Tropical Peat Soils - Sani Babu, Shanthi Devi (1995)
Tropical peat soils are acidic usually with pH values less than 4 and have very low exchangeable bases. The acidity develops as a consequence of dissociation of the functional groups, such as carboxyl and phenolic hydroxyl groups attached to the humic substances of organic matter. Liming is a standard practice to alleviate the acidity and to improve the fertility status of the soil. In Malaysia, lime requirement (LR) studies are conducted by relating crop responses to liming, but so far there is no specific method for determining LR in peat soils. Therefore, the following objectives on the LR determination and soil acidity components were formulated.